The Undifferentiation of Mimetic Violence: From Oedipus to COVID-19. Issue 1 (April 2022) - Gebauer, Gunter
Abstract : In the Poetics Aristotle limited the concept of mimesis to the aesthetic relationship between drama and the actions of its mythical models. In the 1970s, having found representations of mimetic relationships in the myths themselves, René Girard argued that they are the cause of a violence that disrupts the mythical communities from within. Later, Girard extended the concept of mimesis to natural processes: By destroying the differences between model and imitation mimetic processes in nature and in the social world unleash violence. In this essay two important examples of dedifferentiation are discussed and compared: Sophocles' Oedipus dramas and the COVID-19 pandemic crisis in our present time. In both examples, successive mimetic processes subvert the natural and economic foundations of the state, and primarily its framework of rights and duties. The pandemic process destroys the biological, political, and social systems of differences and gives rise to fights for domination over the state.